When the Curtain Falls: Problems of the Subject and Identity as Psychological Infrastructures Collapse - Majumdar, Stefan (Human arenas: an Interdisciplinary journal of psychology, culture, and meaning, 2022)
In the work of Jacques Lacan (1901–1981), and Jean-Paul Sartre (1905–1980), the self is conceptualised as emergent in a complex of ideational, social, and, symbolic relations. Through the lens of ideas represented in the theory of both figures, a picture of consciousness significantly dependent on extended psychological infrastructures which productively interact with the subject, to produce and maintain identity, emerges. The study focuses on Lacan’s ( 1973 ) conceptualisation of ‘Objet petit a’ as a conceptual heuristic for understanding the formation of identity in the midst of the successful or unsuccessful fulfilment of desires. Additionally, Sartre’s ( 1956 ) use of ‘bad faith’ in accentuating the subject’s self-deception in constructing meaning in identity through unexamined courses of life action and belief is examined. Abrupt and intractable implosions of the infrastructures which both gave rise to and maintain the conditions necessary for the emergence of identity represent significant danger for the psychological integrity of the psychological subject. A close re-examination of identity as interpreted through the theoretical precepts set out in the study is suggested as primary in addressing the subject’s distress.